Use of strategies to enable the spray drying of Lactococcus lactis - Cnossen, Débora Christina (2018)
Among the lactic acid bacteria (LAB) applied in food industry, Lactococcus lactis strains stand out due to its high acidification potential, proteolytic activity, production of flavor compounds and inhibition of pathogens by bacteriocins. In some applications, the use of L. lactis as the starter culture depends on its preservation by dehydration, being the spray drying a promising alternative for this purpose. However, this drying technique is poorly applied to L. lactis due to its low thermoresistance and pronounced cell death during the process. In this context, the aim of this work was to apply strategies to increase the tolerance of L. lactis to spray drying. By screening of drying parameters, the ideal powder parameters (water activity (Aw) = 0.198 and temperature (T °Cpowder) = 52 ° C) were determined to ensure greater survival of cells during drying. In the sequence, the effect of lactose and fat contents on the microencapsulation of L. lactis in dairy matrices was investigated. The results revealed that the supplementation of milk with lactose seems to be ideal to drying of heat-sensitive bacteria. In contrast, the fat content has low contribution on the microorganism preservation. Lastly, by using of ideals drying parameters and encapsulating matrix, the influence of previous application of progressive stresses on the survival of L. lactis to the drying process was evaluated. The results showed an increase on the survival of L. lactis (~112.5%) after spray drying and during storage when exposed to the progressive condition of oxidative stress. Collectively, the results are shown as potential strategies to increase the tolerance of heat-sensitive bacteria to the spray drying process.